Implementasi System Application Product (SAP) Di Indutri Manufaktur - Leni Reviyani (Journal Industrial Manufacturing, 2024)
This study analyzes the implementation of the System Application Product (SAP) in the manufacturing industry with the aim of improving operational effectiveness and efficiency. The method used is qualitative with a descriptive and evaluative approach, through unstructured interviews with informants. The results of the study show that the implementation of SAP has a significant impact on company performance, facilitating efficient planning, procurement, and inventory management processes. Additionally, the migration from the ERP SAP GUI (ECC) for Windows system to SAP S/4HANA Cloud (S4HC) demonstrates improvements in data and information management that support better decision-making. This study also finds that training and the involvement of key users are crucial for successful implementation. Despite facing challenges in the migration process, the long-term benefits of using SAP are highly valuable for enhancing company operations.Â Keywords: SAP, ERP, Implementasi, Manufacturing, Operasionalefficiency, S/4HANA Cloud